Alternative strategy for TAVR in the context of limited peripheral vascular access: a case report - Liang Liu; Yi-Jing Guo; Xian Jin (Frontiers in Cardiovascular Medicine)
BackgroundSevere aortic valve stenosis (AS) has become one of the leading causes of mortality in elderly patients. Currently, transcatheter aortic valve replacement (TAVR) has emerged as a crucial treatment strategy for patients with severe AS. However, numerous patients face difficulties receiving TAVR procedure due to individual patient characteristics and peripheral vascular conditions.Case reportWe present a case report of an elderly patient with low body weight and low-risk severe AS. In this patient, the peripheral blood vessels, particularly both iliac arteries, exhibited a notably small diameter throughout. Additionally, the aortic valve area was reduced, with valve leaflets severely calcified, significantly compromising their mobility. The patient opted for TAVR procedure. However, the traditional femoral-iliac approach for TAVR was constrained by the patient's peripheral vasculature and low BMI. Consequently, we established an artificial vascular-common iliac artery pathway as the primary access route for completing the procedure. Intraoperatively, the retrograde guidewire failed to traverse the patient's valve. As a result, an antegrade approach was adopted in combination with an in vitro guidewire capture technique, and ultimately, the TAVR operation was completed.ConclusionOur case demonstrates an innovative interventional treatment strategy for TAVR in patients with severe AS, peripheral vascular limitations, and a low BMI, for whom retrograde wire passage through the valve is not feasible.